Nakupovalna središča v Sloveniji - Drozg, Vladimir (Geografski vestnik, 2001)
Shopping centres represent a new phenomenon in Slovene towns. The first ones at the end of the 1980s, but the majority were built between 1997 and 1999. The total surface of shopping areas in shopping centres increased from a modest 10.000 m2 in 1993 to 280.000 m2 in 1999, which amounts to almost a quarter of all shopping areas in Slovenia.
Keywords: Slovenia; Slovenija; naselja; geografija naselij; centralna naselja; oskrbne dejavnosti